Does Object Height Affect the Dart Throwing Motion Angle during Seated Activities of Daily Living?. Issue 4 (3rd July 2020) - Kaufman-Cohen, Yael; Portnoy, Sigal; Levanon, Yafa; Friedman, Jason
Abstract: Complex wrist motions are needed to complete various daily activities. Analyzing the multidimensional motion of the wrist is crucial for understanding our functional movement. Several studies have shown that numerous activities of daily livings (ADLs) are performed using an oblique plane of wrist motion from radial-extension to ulnar-flexion, named the Dart Throwing Motion (DTM) plane. To the best of our knowledge, the DTM plane angle performed during ADLs has not been compared between different heights (e.g. table, shoulder and head height), as is common when performing day-to-day tasks. In this study, we compared DTM plane angles when performing different ADLs at three different heights and examined the relationship between DTM plane angles and limb position. We found that height had a significant effect on the DTM plane angles - the mean DTM plane angle was greater at the lower level compared to the mid and higher levels. A significant effect of shoulder orientation on mean DTM plane angles was shown in the sagittal and coronal planes. Our findings support the importance of training daily tasks at different heights during rehabilitation following wrist injuries, in order to explore a large range of DTM angles, to accommodate needs of common ADLs.